Pragmatic Awareness in EFL Context: An Assessment on English Literature Students - Fachria Yamin Marasabessy; Sartika Putri Sailuddi; Indry Widyasti Anwar (EDUKASI, 2023)
The purpose of the research was to explore students’ pragmatic awareness and their ability in recognizing grammatical and pragmatic problematic scenarios. There were 25 B2 level students of English Literature study program participated in the study. All students were in their forth year of study and have completed Pragmatics course. The participants were asked to read 15 scenarios of judgment task and to decide whether the given scenarios presented pragmatic or grammatical problem or were unproblematic. The result revealed that the participants were better in recognizing pragmatic problems, followed by the identification of unproblematic scenarios and lastly, participants’ were weakest at recognizing grammatical errors.